2021
DOI: 10.1177/09544089211056033
|View full text |Cite
|
Sign up to set email alerts
|

Analytical derivation of thread profile in internal thread milling process

Abstract: Thread milling is a new machining process as compared to thread tapping. As a thread making process in use for a long time, thread tapping did not have any alternative processes except the thread turning for limited cases until computer numerical control (CNC) technology had enabled the three axes synchronized motion. Therefore, investigations about the thread milling process are less as compared to other machining processes. In this work, the thread profile in the internal thread milling process was derived a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…It is also the first time to analyze the thread surface roughness of high -speed thread milling using a high-precision optical profiler, and found that the thread surface quality is effectively improved by increasing the cutting speed, controlling the feed rate within 0.41-0.45m/min, and the cutting fluid pressure within 2-3.5bar. Dogrusadik [23] derived the thread profile generated by the thread milling process using the analytical method. It is also found that the thread profile produced by the cutter is not the straight line but the curve through the investigation.…”
Section: Introductionmentioning
confidence: 99%
“…It is also the first time to analyze the thread surface roughness of high -speed thread milling using a high-precision optical profiler, and found that the thread surface quality is effectively improved by increasing the cutting speed, controlling the feed rate within 0.41-0.45m/min, and the cutting fluid pressure within 2-3.5bar. Dogrusadik [23] derived the thread profile generated by the thread milling process using the analytical method. It is also found that the thread profile produced by the cutter is not the straight line but the curve through the investigation.…”
Section: Introductionmentioning
confidence: 99%